PENGEMBANGAN MODEL PEMBELAJARAN BAHASA EKSPRESIF BERBASIS ROLE PLAYING PADA ANAK USIA TAMAN KANAK-KANAK - Marwah; Henny; Siti Misra Susanti; Viola (LPPM IAD Probolinggo, 2026)
This study aims to develop and test the effectiveness of a role-playing-based expressive language learning model for kindergarten-aged children. The research problem is motivated by the limited number of language learning activities that provide opportunities for children to actively engage in verbal interaction. This study employed a Research and Development (R&D) method, with the stages of needs analysis, model design, limited trials, evaluation, and product refinement. The subjects were children aged 5–6 years old in Group B at a preschool. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted qualitatively through data reduction, data presentation, and conclusion drawing. The results indicate that the application of a role-playing-based expressive language learning model can improve children's ability to express ideas and feelings, enrich vocabulary, construct simple sentences, increase speaking confidence, and respond appropriately to interlocutors. This learning model is considered effective and aligns with the developmental characteristics of early childhood and the principles of child-centered learning in the Independent Curriculum.